Strategic Management in the Wine Tourism Industry Competitive Strategies, Wine Tourism Behaviour and New Strategic Tools - Martínez-Falcó, Javier; Marco-Lajara, Bartolomé; Sánchez-García, Eduardo; Millán-Tudela, Luis A. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XXVIII, 229 p. 18 illus., 13 illus. in color.